Religious Pluralism in Practice: Defining Secularism in Kenya’s Headscarf Cases (Strathmore Law Journal, 2017)
Present day Kenyan society represents a plurality of peoples, ideas and consequently, approaches to life, a state well embodied in the Constitution of Kenya. The apparent diversity presents challenges to the preservation of the multi-coloured nature of the society and at the same time guaranteeing rights and freedoms as envisaged by the 2010 Constitution. The preamble to the Constitution reconciles the two interests by celebrating the ‘ethnic, cultural and religious diversity’ of Kenya and envisioning an existence ‘in peace and unity as one indivisible sovereign nation’. A marriage of diversity and peaceful coexistence requires tolerance in order to balance competing rights. Within Kenya’s plural society, the most visible religion freedom disputes have been between the Christian majority and Muslim minority. Present constitutional clashes between the two religions date back to the Constitution of Kenya, 1963 (Independence Constitution) and its 1969 revision (Repealed Constitution), which granted Kadhis’ courts limited jurisdiction within a 10-mile coastal strip of the country. Following heated debate on matters of religious pluralism during the constitutional review process, the 2010 Constitution introduced a more accommodative framework for religious freedom. These matters will be analyzed in the following lines.